A Critical Study of Relationships of Predators and Parasitic Infections in Wildlife Animals: Exploring the impact of environmental change on predator-prey dynamics and parasitic infections in wildlife animals (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Due to environmental change, there is less food available, putting wildlife in peril. The majorityof big mammals change their eating habits to accommodate their physiological and reproductiverequirements, and when a desired food source is scarce, the animals are more prone to disease. Theseanimals sometimes leave their natural habitat in quest of food, invade neighboring environments, andoccasionally come into touch with ill household animals. Additionally, they could start consuminganything that is put in front of them, which might be deadly. Living a parasitic lifestyle involves a widerange of various factors. Bencounter filters Bcompatibility filters are part of Combes' complete theoryof Bfilters, which explains the basics governing the development of host-parasite cohabitation.